2013
DOI: 10.1152/japplphysiol.00143.2013
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of neutrophils after endurance exercise reveals novel signaling mechanisms in the immune response to physiological stress

Abstract: AC. Transcriptome analysis of neutrophils after endurance exercise reveals novel signaling mechanisms in the immune response to physiological stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 57 publications
8
69
0
3
Order By: Relevance
“…HSPA1A. Similar results were obtained by Neubauer et al [14]) who examined gene expression 2h after exercise consisting of 1h running and cycling. Furthermore, some authors reported lower levels of HSPA1A expression in trained subjects in comparison to untrained group, as measured after physical activity [14,15].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…HSPA1A. Similar results were obtained by Neubauer et al [14]) who examined gene expression 2h after exercise consisting of 1h running and cycling. Furthermore, some authors reported lower levels of HSPA1A expression in trained subjects in comparison to untrained group, as measured after physical activity [14,15].…”
Section: Introductionsupporting
confidence: 85%
“…Radom-Azik et al [13] and Neubauer et al [14] stated that the upregulation of genes related to apoptosis and immune response in neutrophils, represents an integrated response to various physiological dysfunctions. The presented results, obtained from the experiment which was carried out under heat-stress conditions, are consistent with those reported by Neubauer [14] and Buttner [15], who noted lower expression of genes encoding HSPs and interleukins in trained vs. untrained people after exercise using the same load.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the Hsp, additional sterile inflammation signals released into the circulation by stressed or/and injured cells not assessed in the current investigation may also influence TLR signaling pathways in PBMCs. In this line, Neubauer et al (2013) suggest that DAMPs, hypothetically originating from damaged skeletal muscle tissue, are associated with the activation of TLRs in neutrophils. Moreover, it is important to highlight that the function of these endogenous "danger signals" might be also altered with aging, as a result of increased oxidative stress and inflammation in old subjects (Murlasits et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other structures, called damage-associated molecular patterns (DAMPs), that are endogenous ligands released from damaged or stressed host tissue which also modulate the activation of both TLRs (Asea et al 2002). Under normal physiological conditions, these factors are hidden, but after a stress stimulus, they are released into the extracellular environment to be recognized by the host immune system (Neubauer et al 2013). Numerous studies have showed that apoptotic and necrotic cells release DAMP molecules such as high-mobility group box-1 (HMGB1), S-100 proteins, heat shock proteins, hyaluronan, surfactant protein, interferon-alpha, uric acid, fibronectin, beta defensin, and cardiolipin, which trigger a "sterile inflammatory response" following tissue damage (Martin-Murphy et al 2010;Neubauer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation